Nutritional strategies to reduce methane emissions from cattle: Effects on meat eating quality and retail shelf life of loin steaks. (July 2019) - Richardson, Ian; Duthie, Carol-Anne; Hyslop, Jimmy; Rooke, John; Roehe, Rainer
Abstract: Increasing the lipid concentration and/or inclusion of nitrate in the diet of ruminant livestock have been proposed as effective strategies to reduce the contribution of methane from the agricultural sector to greenhouse gas emissions. In this study, the effects of increased lipid or added nitrate on beef eating quality were investigated in two experiments. In experiment 1, lipid and nitrate were fed alone with two different and contrasting basal diets to finishing beef cattle. In the second experiment, lipid and nitrate were fed alone or in combination with a single basal diet. The sensory properties and retail colour shelf life of loin muscle samples obtained were then characterized. Overall, neither lipid nor nitrate had any adverse effects on sensory properties or colour shelf life of loin muscle.